The Preparation of Molecularly Imprinted Polymers and the Application in Pharmaceutical Analysis - Lan, Ziyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Molecular imprinting technology (MIT) is an artificial method for preparing polymers with specific recognition of target molecules. Molecularly imprinted polymers (MIPs) have been widely used in electrochemical sensors due to their simple preparation, good stability, and molecular recognition function. Especially in drug analysis, MIPs-based electrochemical sensors have become a research hotspot. Therefore, this work focuses on MIPs-based electrochemical sensors. The performance of MIPs is closely related to their preparation methods. In this work, the preparation methods of MIPs are discussed in detail. This work also discussed MIP-based electrochemical sensors. MIP-based electrochemical sensors have achieved accurate detection in flavonoid and antibiotic drugs. Meanwhile, as a polymer, MIPs can also have an impact on the conductivity of working electrode. Therefore, it is necessary to choose some nanomaterials with excellent conductivity for its modification. In the future, molecular imprinting technology will have more applications in electrochemical sensors. In drug analysis, more imprinting targets should be explored for detection by using this technology.